A Bibliometric Analysis of Short Form Video Marketing - Loso Judijanto (West Science Interdisciplinary Studies, 2025)
This study aims to map and synthesize the intellectual structure, thematic evolution, and collaboration patterns in short-form video marketing research through a bibliometric analysis. Using data retrieved from the Scopus database covering publications from 2010 to 2025, this study applies bibliometric and network visualization techniques with the aid of VOSviewer. The analysis examines keyword co-occurrence, citation impact, co-authorship networks, institutional affiliations, and country-level collaborations to identify dominant research themes and emerging trends. The results reveal that short-form video marketing research is strongly centered on social media platforms—particularly TikTok and Douyin—with a growing emphasis on consumer behavior, purchase intention, and digital engagement. Recent studies increasingly focus on platform-specific strategies, advertising embedding, and the role of short-form videos in sectors such as tourism and education. China emerges as the most influential country in terms of research collaboration, while several regional clusters of authors and institutions indicate concentrated but fragmented scholarly networks. Overall, this study provides a comprehensive overview of the development of short-form video marketing literature, offering theoretical insights and practical guidance for researchers and practitioners, while highlighting avenues for future research in this rapidly evolving digital marketing domain.